Emotional Design Analysis in Online Multimedia Learning - Agustin, Atiya Arifiyana; Dewi, Dyah Santhi (Universitas Panca Marga, 2022)
Online learning utilizes multimedia as a learning medium. Emotional factors are often ignored in multimedia learning research. Several studies have stated that emotional factors have a small effect on learning outcomes but have a large effect on student motivation and willingness to learn. Therefore, the emotional factor deserves further investigation of its influence on multimedia learning. Multimedia learning used in the research is in the form of powerpoint (PPT) and video. Emotional factors were measured using the PANAVA-KS method. The best multimedia learning design is a design that can help find a multimedia learning design that can evoke positive emotions so that it can be used as a good learning medium.